Observasi Permainan Untuk Melatih Gerak Lokomotor Pada Siswa SD Negeri 02 Podo, Kedungwuni Pekalongan - Imam Rosada, Faiq Allam; Alfandi, Kurnia; Anggara, Liyant Maihendra; Putri, Mega Widya (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
This observation aims to train agility and dexterity for grade 3 students at SD Negeri 02 Podo so that they have good motor skills. Apart from improving the motor skills of students at SD Negeri 02 Podo, it also aims to achieve healthy and strong body fitness. Observation results show that improving motor movements taught at SD Negeri 02 Podo, Kedungwuni, Pekalongan has several advantages but also has disadvantages. The advantages include applying several fun manipulative movement training methods, while the weaknesses include the lack of health factors for students at SD Negeri 02 Podo, Kedungwuni, Pekalongan who easily get tired due to a lack of education on healthy lifestyles. Based on the results of observations, recommendations for improvement are proposed to improve the quality of the healthy lifestyle of students at SD Negeri 02 Podo. This observation provides valuable information regarding the importance of motor movements from an early age, which must continue to be motivated and exercised in order to have excellent and of course healthy body movements.